Textbook of uncommon cancer - Raghavan, Derek (John Wiley & Sons, Inc., 2017)
"The fifth edition of the only comprehensive text dealing exclusively with rare or infrequently encountered malignancies in adults and children is an essential resource for any clinical oncologist. Encompasses all the information needed to diagnose and manage uncommon cancers, an area where advice and guidance is typically scarce Fully revised with new material and an evidence-based, teach-by-example approach Provides insight on real-world decision making in the clinical setting Edited and authored by a highly experienced and senior team of medical oncologists, radiation oncologists, and other specialists, giving a balanced and complete overview Extensively illustrated in full color throughout, including heat maps to show gene expression"-Resumé vydavatel